Benefits and harms of pregabalin in the management of neuropathic pain: a rapid review and meta-analysis of randomised clinical trials - Igho J Onakpoya; Elizabeth T Thomas; Joseph J Lee; Ben Goldacre; Carl J Heneghan (BMJ Open)
Objective To assess the benefits and harms of pregabalin in the management of neuropathic pain.Design Rapid review and meta-analysis of phase III, randomised, placebo-controlled trials.Participants Adults aged 18 years and above with neuropathic pain defined according to the International Association for the Study of Pain criteria.Interventions Pregabalin or placebo.Primary and secondary outcome measures Our primary outcomes were pain (as measured using validated scales) and adverse events. Our secondary outcomes were sleep disturbance, quality of life, Patient Global Impression of Change, Clinician Global Impression scale, anxiety and depression scores, overall discontinuations and discontinuations because of adverse events.Results We included 28 trials comprising 6087 participants. The neuropathic pain conditions studied were diabetic peripheral neuropathy, postherpetic neuralgia, herpes zoster, sciatica (radicular pain), poststroke pain and spinal cord injury-related pain. Patients who took pregabalin reported significant reductions in pain (numerical rating scale (NRS)) compared with placebo (standardised mean difference (SMD) −0.49 (95% CI −0.66 to −0.32, p<0.00001), very low quality evidence). Pregabalin significantly reduced sleep interference scores (NRS) compared with placebo (SMD −0.38 (95% CI −0.50 to −0.26, p<0.00001), moderate quality evidence. Pregabalin significantly increased the risk of adverse events compared with placebo (RR 1.33 (95% CI 1.23 to 1.44, p<0.00001, low quality evidence)). The risks of experiencing weight gain, somnolence, dizziness, peripheral oedema, fatigue, visual disturbances, ataxia, non-peripheral oedema, vertigo and euphoria were significantly increased with pregabalin. Pregabalin was significantly more likely than placebo to lead to discontinuation of the drug because of adverse events (RR 1.91 (95% CI 1.54 to 2.37, p<0.00001), low quality evidence).Conclusion Pregabalin has beneficial effects on some symptoms of neuropathic pain. However, its use significantly increases the risk of a number of adverse events and discontinuation due to adverse events. The quality of the evidence from journal publications is low.